Randomized phase II study of stereotactic body radiotherapy and interleukin-2 versus interleukin-2 in patients with metastatic melanoma. Issue 1 (27th May 2020) - Curti, Brendan; Crittenden, Marka; Seung, Steven K; Fountain, Christopher B; Payne, Roxanne; Chang, ShuChing; Fleser, Jessica; Phillips, Kimberly; Malkasian, Ian; Dobrunick, Lyn B; Urba, Walter J
Abstract : Background: A pilot study of stereotactic body radiation therapy (SBRT) followed by high-dose interleukin-2 (IL-2) showed a higher than anticipated objective response rate (ORR) among patients with metastatic melanoma (MM). We performed a prospective randomized study to determine if the ORR of SBRT + IL-2 was greater than IL-2 monotherapy in patients with advanced melanoma. Methods: Patients with MM who had adequate physiological reserve for IL-2 and at least one site suitable for SBRT were eligible. There was a 1:1 randomization to SBRT + IL-2 or IL-2 monotherapy. Patients received one or two doses of SBRT (20 Gy per fraction) with the last dose administered 3 days before starting the first cycle of IL-2. IL-2 (600, 000 IU per kg via intravenous bolus infusion) was given every 8 hours for a maximum of 14 doses with a second cycle after a 2-week rest. Responding patients received up to six IL-2 cycles. Patients assigned to IL-2 monotherapy who exhibited progression of melanoma after cycle 2 were allowed to crossover and receive SBRT and additional IL-2. Response Evaluation Criteria in Solid Tumors 1.1 criteria were applied to non-irradiated lesions for response assessment. Results: 44 patients were included in the analysis. The ORR in the SBRT + IL-2 group was 54%: 21% complete response (CR), 33% partial response (PR), 21% stable disease (SD) and 25% progressive disease (PD). The ORR in patients receiving IL-2 monotherapy was 35%: 15% CR, 20% PR, 25% SD and 40% PD. Seven patients assigned to IL-2 subsequently received SBRT + IL-2. One CR and two PRs were observed in the crossover group. There was no difference in progression-free or overall survival (OS). At 5 years the OS was 26% in the SBRT + IL-2 group and 25% in the IL-2 monotherapy group. The disease control rate (DCR) was higher in the SBRT + IL-2 group (75% vs 60%, p=0.34). Conclusions: SBRT + IL-2 induced more objective responses with a higher DCR compared to IL-2 monotherapy in MM. IL-2 monotherapy resulted in a significantly higher ORR than anticipated. Some patients in the crossover group also achieved objective responses. Trial registration number: NCT01416831 .